马来西亚华人[ʂ]音在不同上下文中的发音变化及其社会意义 = An investigation of Malaysian Chinese [ʂ] sound in different contexts and its social significance - 陈联樱 Chan, Lian Yin (2010)
在普通话或华语里，某个字词的翘舌发音往往在不同的上下文受到相邻前或相邻后的字音或词音影响而产生发音变化。本文通过对42位马来西亚华人的语音采样，主要考察“是”字在不同的上下文中的发音变化。在数据整理方面，运用PRAAT语音软件，以两位中国普通话水平测试员的发音为判断标准，评判被试的强频区下限频率， 再加上问卷调查，归纳马来西亚华人的 [ʂ] 翘舌音可分为“重度翘舌音”、“轻度翘舌音”和“没有翘舌音”三种变式，并对“是”处于单音节词或双音节词组合的位置时的发音进行了对比分析，然后计算四种社会变量包括方言、居住地、性别和教育背景分别对马来西亚 [ʂ] 翘舌音的影响，借以探讨马来西亚华人 [ʂ] 翘舌音的发音特色和其社会意义。 A retroflex sound mainly lies on the adjacent syllables in different contexts in Mandarin. Based on the voice sampling recorded from a group of 42 Malaysian Chinese, this research is aimed to study how the different possible ways of pronouncing the word shi（是） in different contexts. Using the pronunciations by two test controllers from the China National Proficiency Test of Putonghua as a standard reference, together with the PRAAT phonetic software application, the data collected via recordings of answers to the questionnaire, designed for this study revealed that the sound [ʂ] uttered by Malaysia Chinese has three variants – strong [ʂ], weak [ʂ], and no [ʂ]. In addition, a comparison was made between the pronunciation of shi when uttered as a one syllable word and that when uttered together with another syllable as a double syllable compound. The contributing factors for the three variants of the [ʂ] pronunciation were examined with reference to dialect influence, gender, geographical region and education. The social significance of such differences was discussed as well.